A study of the pion–nucleon coupling constant based on scattering length and effective range for both pseudovector and pseudoscalar (Journal of Pure and Applied Sciences (Science Forum), 2026)
In this study, we critically evaluate the Yukawa potential using the meson field theory in order to establish a relationship between the energy (MeV) for both neutron–proton and proton–proton which is pseudoscalar and pseudovector in the case of scattering field, similar in the effect range from experimental values of pion atoms. We also deduce the charged pion–nucleon coupling constant systematically and with statistical uncertainties. The result shows that both models display good agreement with the experimental values with a trend as the energy increases for both interactions’ effective range on pseudovector (proton–proton) and pseudoscalar (neutron–proton) is at a smaller length. Similarly, low energy is recorded for the scattering length interaction. The charge pion–nucleon coupling constant is at values of 214.54 4gππ±and 214.52 4gππ±for both pseudovector and pseudoscalar, respectively. This shows that the electromagnetic interaction associated with the correction will likely be added or removed from the experimental values of the nuclear-Coulomb low-energy parameters of pp and np scatteringPACS numbers: 13.75.Cs, 13.75.G×, 14.20.Dh, 14.40.Be, 25.40.Cm, 25.40.Dn.